Typology of hybrid panel and modular housing systems - Mukasheva, Madina (project baikal, 2026)
The work is devoted to the analysis of the adaptability of mass housing in conditions of climatic and seismic constraints. The purpose of the study is to develop an architectural and typological tool for assessing the adaptive potential of hybrid panel and modular systems. The study applies typological and comparative analytical methods based on the analysis of the interaction of load-bearing structures and filling elements. As a result, the author proposes a typology of hybrid residential systems, which reveals differences in the distribution of spatial rigidity and transformation possibilities. The study shows the dependence of architectural flexibility on the context in the conditions of industrialized construction.